A STUDY ON TOURISM IN RAJASTHAN - Mishra, Aarti; Goswami, Ruchi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The land of dessert Rajasthan is famous for its rich culture, royalty, heritage, folk music, folk dance, delicious food, jams and jewelry, traditional attire etc. The state is flourishing with haweli architecture, forts, palaces, step wells, temples and many more historical monuments. Earlier, the capital of Rajputana was Amber, but later on the Pink City, Jaipur became the official capital of the state. The beauty of the city is incredible but it got the popularity through various Bollywood, Hollywood movies. The film makers have had unveiled the charm of the state that one had never done before. The study focuses on how the film induced tourism is flourishing and flaunting the state on national and international map respectively. The amount of footprint witnessing every year after getting inspired from the films and the features of Rajasthan film tourism promotion policy have also been discussed for the betterment of both the tourism and entertainment industry. This study is a binding modification of different exploration studies and articles composed by numerous researchers, authors and writers.